Undertreatment of cardiovascular risk factors in the type 1 diabetes exchange clinic network (United States) and the prospective diabetes follow‐up (Germany/Austria) registries. Issue 9 (19th May 2020) - Shah, Viral N.; Grimsmann, Julia M.; Foster, Nicole C.; Dost, Axel; Miller, Kellee M.; Pavel, Marianne; Weinstock, Ruth S.; Karges, Wolfram; Maahs, David M.; Holl, Reinhard W.
Abstract: Aim: To examine the control of cardiovascular risk factors in type 1 diabetes (T1D) registries from the United States and Germany/Austria. Materials and Methods: Data on individuals aged ≥12 years with T1D for ≥1 year, from the T1D Exchange Clinic Network (T1DX, United States) and the Prospective Diabetes Follow‐up Registry (DPV, Germany/Austria) from 1 January 2016 to 31 March 2018 were analysed. Linear and logistic regression models adjusted for age groups, sex, duration of diabetes and minority status were used to compare clinical characteristics and achievement of diabetes management targets between registries. Results: The cohort consisted of 47 936 patients (T1DX, n = 19 442; DPV, n = 28 494). Achievement of HbA1c goals (<7.0%, ages 18‐65 years; all others, <7.5%) was better in the DPV for those aged <65 years (all P  < .001). However, more older adults (aged ≥65 years) in the T1DX achieved an HbA1c goal of <7.5% compared with DPV (70% vs. 50%, P  < .001). The frequency of patients with overweight (53% vs. 51%, P  < .001) and obesity (19% vs. 9%, P  < .001) was higher in T1DX. The frequency of meeting blood pressure goals (84% vs. 66%, P  < .001) and lipid goals (73% vs. 62%, P  < .001) was higher in T1DX; this was observed across all age groups (all P  < .001). Few young adults aged <26 years received antihypertensive and lipid‐lowering medications, respectively, despite indications in both registries (T1DX: 5% and 3%, DPV: 3% and 1%). Conclusion: A minority of patients with T1D achieve glycaemic targets and the majority are inadequately treated for hypertension and dyslipidaemia. This highlights the need for improved diabetes and cardiovascular risk management strategies in T1D.